2006
DOI: 10.1016/j.ecolmodel.2006.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of trophic structure and interactions of two tropical lagoons

Abstract: A comparative study of the Ébrié lagoon (Ivory Coast) and Lake Nokoué (Benin) was made based on ecotrophic model outputs that describe each system's structure and functioning. Two models were constructed using the Ecopath software to differentiate main biomass flows in the systems.Results indicate that biomasses and productions in both ecosystems are concentrated in trophic levels (TL) 2 and 3. Higher TL biomasses and productions in Lake Nokoué compared to Ébrié lagoon may be explained by the presence of acadj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
49
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 66 publications
12
49
1
Order By: Relevance
“…Relative overhead is dimensionless and therefore suitable for comparison purposes. The PRD coastal ecosystem has similar value of relative overhead (66.5%) to Ébrié lagoon (67.0%) [57], which indicates that the system was likely to be more susceptible to stress -induced changes and need longer time to recover from unexpected perturbations.Ecopath can yield the prey overlap index and predator overlap index between every two groups included in the model (Fig. 2).…”
mentioning
confidence: 70%
“…Relative overhead is dimensionless and therefore suitable for comparison purposes. The PRD coastal ecosystem has similar value of relative overhead (66.5%) to Ébrié lagoon (67.0%) [57], which indicates that the system was likely to be more susceptible to stress -induced changes and need longer time to recover from unexpected perturbations.Ecopath can yield the prey overlap index and predator overlap index between every two groups included in the model (Fig. 2).…”
mentioning
confidence: 70%
“…Eutrophic processes would decrease the information diversity in an ecosystem and lead to relatively low level of ascendency. In this study, because of the low value of AMI (0.929) in Lake Dianchi, the value of ascendency (25.3%) was similar to that of the eutrophic Lake Taihu (25.7%) and Northern Adriatic Sea (24.7%) (Li et al, 2009a,b;Coll et al, 2007), and was considerably lesser than that of the relatively oligotrophic ecosystems such as Lake Qiandao (33.4%) and Évbrié lagoon (34.0%) (Villanueva et al, 2006;Liu et al, 2007).…”
Section: Cycling and Information Indicesmentioning
confidence: 99%
“…P represents primary producers, including phytoplankton and macrophytes. was considerably larger than that of the eutrophic Lake Taihu in the 1990s (11.66 year −1 ) and Lake Nokoné (23.78 year −1 ; Li et al, 2009a,b;Villanueva et al, 2006). Brando et al (2004) suggested that, the higher the TST value, the more rapid is the turnover rate of biomass of the entire ecosystem.…”
Section: Ecosystem Propertiesmentioning
confidence: 99%
“…Accessibility rules between predator-prey compartments were determined based on expert knowledge and mainly based on qualitative stomach content analysis and other studies in similar environments (Villanueva et al 2006). The original predation hypothesis in OSMOSE is that each fish can eat a potential prey defined in an interval between two fractions of its own length.…”
Section: Predationmentioning
confidence: 99%
“…Because of natural defences, the accessibility of the African sea catfish group to predation was set at 0 for any potential predator except sharks reported to feed on the African sea catfish. The predation rates for each species, defined as the biomass of prey per unit biomass of predator required to ensure physiological needs of predatory individuals were taken from ECOPATH estimates (Villanueva et al 2006) and ranged from 5 (very large predators) to 32 (tilapines). Critical predation efficiency, i.e., the minimal rate of biomass ingestion over the needed biomass to allow individual growth, and maximum starvation mortality rate, i.e.…”
Section: Predationmentioning
confidence: 99%